Analisis Pengendalian Food Waste Pasca Produksi pada Layanan Dinner Buffet di Pavilion Restaurant JW Marriott Hotel Surabaya - Efendi, Ahmat Dafid; Purwidiani, Niken; Dewi, Ila Huda Puspita; Kamiliya, Aisyah Nurin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Post-production food waste is a common issue in hotel dinner buffet services due to leftover food remaining after service has ended. This study aims to examine the condition of post-production food waste, the control measures implemented, and the indicators of successful post-production food waste control in the dinner buffet service at Pavilion Restaurant, JW Marriott Hotel Surabaya. This study employed a descriptive qualitative method, with data collected through interviews, observations, documentation, and post-production food waste weighing conducted over a 10-day observation period. The findings indicate that post-production food waste originated from leftover food on the buffet line, food remaining after service, and food that could not be reused due to food safety standards. The contributing factors included overproduction, the characteristics of buffet service, inaccurate buffet replenishment, and the implementation of food safety standards. The total post-production food waste generated during the study was 46.111 kg, with an average of 4.611 kg per day. Food waste control was implemented through production planning, guest forecasting, Final Guest Count, Standardized Recipes, Portion Control, Batch Cooking, buffet replenishment, and buffet line monitoring. The success of food waste control was indicated by production accuracy, reduced overproduction, and a reduction in post-production food waste, thereby improving operational efficiency and minimizing food waste in the dinner buffet service